(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
The study of how images affect the human brain and visual perception draws from neuroscience, psychology, and art. It investigates how visual content influences emotions, body responses, and thought processes. In the Electronic Era, theater has sought to create a mental space using technology, often making its language inseparable from the message and disconnected from its usual context. This article analyzes the effects of digital visuals and technology in theater on viewer perception. It looks at how images can trigger specific emotions and the influence of immersive, virtual, and interactive content on consciousness and physical responses. Images serve as stimuli that engage the mind, linking psychological reality with sensory and intellectual experiences. Viewing these images helps people access various emotions, as the brain combines them with past experiences and emotional patterns. Research shows that emotionally charged images activate the limbic system and prefrontal cortex in the brain. The potential for performing arts to evoke strong emotional responses through digital elements leads to profound experiences that go beyond time and space. Ultimately, images are potent tools that shape sensory and mental experiences in theater and art